Math, asked by Ansarirazi, 5 months ago

solve the following equation
3 ( x + 2 ) = 2 ( x + 1 )​

Answers

Answered by ItzMeMukku
14

\bold{\boxed{HEY!!!}}

HERE IS YOUR ANSWER :-

3 ( x + 2 ) - 2 ( x - 1 ) = 7

=> 3x + 6 - 2x + 2 = 7

=> x + 8 = 7

=> x = 7 - 8

=> x = - 1

\bold{\boxed{x=-1}}

\underline{VERIFICATION}

x = - 1

On L.H.S.

3 ( - 1 + 2 ) - 2 ( - 1 - 1 )

= 3 × 1 - 2 × ( - 2 )

= 3 + 4

= 7

= R.H.S.

Hence verified.

Answered by lovinglavisha
16

3 ( x + 2 ) = 2 ( x + 1 )

3x+6=2x+2

3x-2x=2-6

x= -4

hope it would be helpful for you plz mark me as brainliest

Similar questions